Single dc source diode-assisted hybrid multilevel inverter using a reduced number of active and passive components - Motwani J.K.; Routray A.; Singh R.K.; Mahanty R. (My University, 2025)
In this study, a seventeen-level diode-assisted hybrid multilevel inverter (DAH-MLI) is proposed. The DAH-MLI eliminates any external voltage balancing and/or sensing circuit by inherently balancing the capacitors using a series-parallel combination of capacitors and DC voltage source. The DAH-MLI uses only one DC source and a reduced number of active and passive elements to generate a multilevel staircase output voltage. The proposed circuit can also be extended to obtain the higher number of voltage levels than seventeen by the addition of a single module comprising of two diodes, one switch, and one capacitor. The proposed DAH-MLI can boost the input voltage and possesses reverse current carrying capability. The proposed DAH-MLI is compared with several existing topologies on the basis of the number of active and passive components, total standing voltage, and peak inverse voltage to verify its advantages. A cost function is used in this study to compare the proposed DAH-MLI and other existing typologies. Finally, the performance of the proposed DAH-MLI is validated through a 570 W experimental prototype. © The Institution of Engineering and Technology 2020.